2006
DOI: 10.1002/jmri.20794
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI lesion classification: Improved performance of human readers with a backpropagation neural network computer‐aided diagnosis (CAD) system

Abstract: Purpose:To develop and test a computer-aided diagnosis (CAD) system to improve the performance of radiologists in classifying lesions on breast MRI (BMRI). Materials and Methods:A CAD system was developed that uses a semiautomated segmentation method. After segmentation, 42 features based on lesion shape, texture, and enhancement kinetics were computed, and the 13 best features were selected and used as inputs to a backpropagation neural network (BNN). The BNN was trained and tested using the leave-one-out met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 31 publications
(39 reference statements)
4
85
0
Order By: Relevance
“…A typical breast DCE-MRI contains a great amount of heterogeneous information that depicts different tissues, vessels, ducts, chest skin, and breast edge characteristics. Texture features have been widely used in breast DCE-MRI mass classification 7,18,[32][33][34][35][36][37] . The implemented feature extraction procedure relies on the exploration of the textural characteristics of the extracted mass.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical breast DCE-MRI contains a great amount of heterogeneous information that depicts different tissues, vessels, ducts, chest skin, and breast edge characteristics. Texture features have been widely used in breast DCE-MRI mass classification 7,18,[32][33][34][35][36][37] . The implemented feature extraction procedure relies on the exploration of the textural characteristics of the extracted mass.…”
Section: Feature Extractionmentioning
confidence: 99%
“…15, which is used to extract the edges of the tumour very efficiently in segmented MR images, followed by proper threshold for extraction the lesion or region of interest (ROI) from edge enhanced segmented breast MR images. After detection of the ROI, statistical analysis techniques are applied to select an optimal set of features to achieve the highest diagnostic accuracy [16][17][18] . The extracted features are fed as input to the classifier to discriminate whether the lesion is benign or malignant.…”
Section: Introductionmentioning
confidence: 99%
“…For integrating all extracted morphologic and dynamic features, ANNs were used (21,23,24). Feed-forward selfreflexive ANNs had been trained in advance of this investigation on the list of the above-described morphologic and dynamic parameters.…”
Section: Classification Of Lesionsmentioning
confidence: 99%
“…Although recent developments have focused on the automatic, computerassisted analysis of morphologic MRM features, eg, by the use of a classification tool, such as an artificial neural network (ANN), clinical assessment of MRM is still based on the observer's interpretation of morphology (11,13,15,(21)(22)(23)(24). There is clinical interest to integrate observer-independent morphologic analysis into ubiquitously available CAD systems and to link the computer-extracted features to the BI-RADS descriptors.…”
mentioning
confidence: 99%
“…The CAD schemes first extract and compute dynamic contrast enhancement features from the characteristic kinetic curves generated from a set of the selected pixels located inside the identified and segmented breast lesions, and then apply different machine learning classifiers to distinguish between the malignant and benign lesions [16][17][18][19][20]; for example, one study reported that using a leave-one-case-out testing method, a CAD scheme using a set of selected DCE-MRI features and a Bayesian artificial neural network yielded an area under a receiver operating characteristic (ROC) curve (AUC=0.78±0.04) when applying to a dataset involving 168 malignant and 45 benign breast lesions [21]. Although the previous studies focused on detection and analysis of characteristic kinetic curves computed from the pixels inside the segmented lesions, a recent study also showed that similar to a widely used image-based risk factor, namely, the mammographic density, the background parenchymal enhancement (BPE) evaluated or computed from the entire breast areas depicting on DCE-MRI images also carried useful or higher discriminatory information associated with cancer risk assessment [22] as well as the performance of cancer detection and staging [23].…”
Section: Introductionmentioning
confidence: 99%